2021
DOI: 10.1002/adfm.202105911
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Responsive and Low‐Energy‐Consumption Poly(3‐hexylthiophene)/Perovskite Quantum Dots Composite Film‐Based Photonic Synapse

Abstract: Emulation of photonic synapses through photo-recordable devices has aroused tremendous discussion owing to the low energy consumption, high parallel, and fault-tolerance in artificial neuromorphic networks. Nonvolatile flash-type photomemory with short photo-programming time, long-term storage, and linear plasticity becomes the most promising candidate. Nevertheless, the systematic studies of mechanism behind the charge transfer process in photomemory are limited. Herein, the physical properties of APbBr 3 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…Notably, the FA‐QDs/P3HT photosynaptic transistor exhibited an ultralow energy consumption of 3 × 10 −17 J with EPSC = 1.2×10 −12 A collected at a V DS of −5 × 10 −4 V and a spike pulse of 5 × 10 −2 s under illumination at 450 nm; this represents state‐of‐the‐art artificial synapse behavior with the lowest energy consumption reported to date. [ 127 ] Subsequently, Ercan et al demonstrated the efficacy of self‐assembled nanostructures in photosynaptic transistors composed of CsPbBr 3 QDs and P3HT. [ 128 ] By introducing marginal solvent of acetonitrile, ultrasonication, and UV treatment to the blending solution of QDs and P3HT, QDs formed aligned coaggregates along with the nanofibrillar P3HT, thereby achieving a decent synaptic performance of a low energy consumption of 1.8 × 10 −16 J with EPSC = 3.6 × 10 −11 A collected at V DS of −0.001 V and a spike pulse of 5 × 10 −2 s under illumination at 450 nm to the previous result.…”
Section: Application Of Phototransistors In Artificial Synapses and P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the FA‐QDs/P3HT photosynaptic transistor exhibited an ultralow energy consumption of 3 × 10 −17 J with EPSC = 1.2×10 −12 A collected at a V DS of −5 × 10 −4 V and a spike pulse of 5 × 10 −2 s under illumination at 450 nm; this represents state‐of‐the‐art artificial synapse behavior with the lowest energy consumption reported to date. [ 127 ] Subsequently, Ercan et al demonstrated the efficacy of self‐assembled nanostructures in photosynaptic transistors composed of CsPbBr 3 QDs and P3HT. [ 128 ] By introducing marginal solvent of acetonitrile, ultrasonication, and UV treatment to the blending solution of QDs and P3HT, QDs formed aligned coaggregates along with the nanofibrillar P3HT, thereby achieving a decent synaptic performance of a low energy consumption of 1.8 × 10 −16 J with EPSC = 3.6 × 10 −11 A collected at V DS of −0.001 V and a spike pulse of 5 × 10 −2 s under illumination at 450 nm to the previous result.…”
Section: Application Of Phototransistors In Artificial Synapses and P...mentioning
confidence: 99%
“…[ 128 ] By introducing marginal solvent of acetonitrile, ultrasonication, and UV treatment to the blending solution of QDs and P3HT, QDs formed aligned coaggregates along with the nanofibrillar P3HT, thereby achieving a decent synaptic performance of a low energy consumption of 1.8 × 10 −16 J with EPSC = 3.6 × 10 −11 A collected at V DS of −0.001 V and a spike pulse of 5 × 10 −2 s under illumination at 450 nm to the previous result. It is worth noting that CsPbBr 3 QD presents lower charge transfer efficiency to P3HT than FAPbBr 3 QDs based on the time‐resolved photoluminescent characteristics, [ 127 ] and therefore, further advancement is expected to be achieved by combining high‐performance QDs and nanostructured engineering to the semiconductors and photogates.…”
Section: Application Of Phototransistors In Artificial Synapses and P...mentioning
confidence: 99%
“…The programming state by photo-writing can be electronically erased by applying a gate bias (V GS ) at −60 V for 1 s and the transfer curve can shift back to initial state due to electrons neutralized by the injected holes. In order to further explain the photon-writing phenomena, the temporal drain current (I DS ) under blue light To further clarify the dynamics of photo-induced charge transfer process for all BCP/perovskite composite films, the photo-responsive current toward time was executed and described by Equation (5).…”
Section: Performance Of Bcp/perovskite-based Photomemoriesmentioning
confidence: 99%
“…Compared to electrically programmed memories, nonvolatile flash photomemory using photon as the firth terminal can store the light information to provide noncontact writing method that simplifies the design of integrated circuit. [1][2][3][4][5] Basically, the photomemory has the same architecture as the floating-gate memory whereas the photoactive and charge-trapping material as a substitute for conventional floating-gate to enable photo-programming capability. Photo-programming process possess phase separation due to the covalent links between two segments, leading to form a variety of ordered nanostructures such as lamellas, cylinders, and spheres by controlling the block ratio or the embedded small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure sensors respond intelligently with the electrical signals in response to the applied pressure. Pressure sensors have been developed into a multidisciplinary field of research, as they interconnect material synthesis, processing, fabrication, system engineering, and signal acquisition, including new technological upgrades such as artificial intelligence and the internet of thing [58][59][60]. Recent trends and a good deal of research interests have evolved with the active involvement of metallic nanostructures, metallic hybrids, carbonaceous material-based sensing, etc., [61][62][63].…”
Section: Pressure Sensors' Working Modementioning
confidence: 99%